Diversidade molecular de Fosfolipases D da peçonha da aranha Loxosceles laeta peruana revelada por sequenciamento de nova geração e análise transcriptômica - Priscilla Alves de Aquino (2016)
This study aims to analyze, by bioinformatic tools, the transcripts of the brown spider venom gland Loxosceles laeta to expand the phospholipase D database. Sequences found through the new generation of sequencing RNA-seq and transcriptome assembly of the program Trinity, were subjected to gene annotation that so they could be identified through searches of similarity against different databases. Then they were classified into functional categories and had their biological function evaluated from a phylogeneticstandpoint. The identification correlated to the venom of compounds promotes better understanding of the pathophysiological processes of envenomation cases, as well as tools for improvements in methods of prophylaxis and treatment for loxoscelism. This dissertation aimed to describe the venom proteins responsible for its major toxic activities, which are the PhospholipaseD, Sphingomyelinase D or Dermonecrotic Proteins. In this study, 19 putative Phospholipase D sequences were described from the venom gland of the spider L. laeta. From the analysis and description of the Phospholipases D expression from the venom and their molecular interaction, it is possible to improve tools for the study of mechanisms of action of dermonecrotic activity of these enzymes. In addition, the in-depth study of the expression of these enzymes favor future studies on the phylogeny of their proteins.